"Influence of storage conditions on phenolic compounds stability, antioxidant capacity and colour of freeze-dried encapsulated red wine". (July 2016) - Rocha-Parra, Diego Fernando; Lanari, María Cecilia; Zamora, María Clara; Chirife, Jorge
Abstract: A concentration of 9% (w/w) maltodextrin (DE 10) and gum arabic was added to red wine C. sauvignon and freeze dried to obtain a dealcoholized wine powder having a polyphenols concentration 7.1 times higher than in liquid red wine. Malvidin 3-G and total anthocyanins were the phenolics showing greater losses during storage. Moreover, an increase of water activity from 0.11 to 0.58 greatly enhanced the losses. The decrease in malvidin 3-G content was associated with the decrease on redness (colour parameter a*) of wine powder. Gallic acid was the most stable phenolic and its content remained constant during storage at all water activity levels under investigation. Contents of epicatechine, catechine, caffeic acid and resveratrol remained constant at aw  = 0.11, although at aw  = 0.33 catechine and epicatechine suffered important losses. Results indicated that water activity was a key factor affecting phenolics stability during storage. Antioxidant activity of the wine powder remained constant over 145 days at accelerated storage conditions. Highlights: Red wine was freeze-dried encapsulated in maltodextrin-Arabic gum. Free flowing powder was obtained and glass transition temperature was determined. Six phenolics, colour and antioxidant capacity followed during storage at 38 °C. Gallic and caffeic acids, catechin, epicatechin, resveratrol, malvidin 3-G studied. Water activity had and important influence on stability of phenolics.